A palavra em estado de ofício: O Ausente, de Edimilson de Almeida Pereira - Romeu, Gabriela (2025)
This study investigates the writing process in Edimilson de Almeida Pereira's novel O Ausente (2020), based on a link between the characters of the poet, the healer (or benzedor) and the ethnographer and their relationship with words. To this end, this research evokes this triad at the root of his work, in which words are the raw material of his craft. The study's hypothesis is that, by tracing the relationships between the three characters, we can unravel the passwords of the author's poetic work and also find the traces of an ethnographic work. By investigating the traces of the poetics of the novel, we seek to establish associations and differentiations between the work of the poet, the benzedor and the ethnographer, as well as analyzing the relationship between the fields of literature and anthropology in the work under investigation. O Ausente (The Absent) is the debut novel from the writer and thinker from Minas Gerais and, despite the considerable critical fortune of his career, spanning almost four decades and dozens of published books, the field of literary studies still lacks research into the prose of this poetanthropologist. The theoretical-critical foundation is based, among others, on the authors: Edimilson de Almeida Pereira himself (2000; 2002; 2003; 2008; 2010; 2017; 2018; 2019; 2020; 2022; 2022b; 2023; 2023b), Leda Maria Martins (1997; 2021), Marília Librandi (2012; 2020), Eduardo Viveiros de Castro (2002), Alexandre Nodari (2015; 2024) and Cecília Salles (2006; 2011)